2017
DOI: 10.12973/eurasia.2017.00760a
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Singaporean versus Indonesian Textbooks Based on Trigonometry Content

Abstract: Organization for Economic Cooperation and Development (OECD) (2016) released the results of Programme for International Student Assessment (PISA) 2015 and reported that the students' performance in mathematics of Singapore and Indonesia had significant differences. There is a strong relationship between textbooks used and mathematics performance of the students. If textbooks differ, students will get a different opportunity to learn and the opportunity to learn influences students' achievement (performance). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
1
18
0
3
Order By: Relevance
“…Broadly speaking, there are differences in the curriculum in Indonesia and Singapore (Lisarani et al, 2018;Yang & Sianturi, 2017). The Singapore Science Curriculum Framework is centred on the spirit of scientific inquiry and is based on three domains that are important for scientific practice: knowledge, understanding and application; skills and processes; and ethics and attitudes (Ministry of Education, 2013b, 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadly speaking, there are differences in the curriculum in Indonesia and Singapore (Lisarani et al, 2018;Yang & Sianturi, 2017). The Singapore Science Curriculum Framework is centred on the spirit of scientific inquiry and is based on three domains that are important for scientific practice: knowledge, understanding and application; skills and processes; and ethics and attitudes (Ministry of Education, 2013b, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in Indonesia, tasks with a combination of representations, non-application tasks, and open-middle tasks are the types that most often appear. While research from Yang and Sianturi (2017) shows that education in Singapore requires higher cognitive abilities than Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Caldwell and Burger, 1998;Saks and Ashforth, 1997). Researchers also studied the impacts of poor person-job fit on workplace behaviors, and they found that poor person-job fit could lead to job dissatisfaction, low organizational commitment and high turnover intention (Boon et al, 2011;Yang and Sianturi, 2017). Following previous studies, the current research examines the relationship between knowledged staff's subjective person-career fit and the knowledged staff's career subjective well-being, the effects of career selfmanagement and support in organization.…”
Section: Introductionmentioning
confidence: 95%
“…The intended curriculum and the implemented curriculum are bridged by textbooks, it helps teachers for planning lessons in the class (Jelić & Đokić, 2017;Reyhani & Izadi, 2018). TIMSS has a result that when teachers select their teaching method they use mathematics textbooks as their main resource especially for tasks and practice exercises (Gracin, 2018;Yang, 2017).…”
Section: Introductionmentioning
confidence: 99%